Stocks or Stakeholders: The Benefits of Considering Animal Interests - Briscoe, Michael, (Human-Animal Studies ;, 2025)
Animals are typically treated as property in modern societies. Stocks or Stakeholders extends stakeholder theories to animals, arguing that full consideration of their interests will benefit humans. For example, one analysis in the book shows that more protected land is associated with fewer animal-vehicle collisions-events that currently cost millions of dollars each year and injure both humans and animals. Regardless of how readers personally feel about animals, Stocks or Stakeholders makes a compelling case for seriously considering their interests.